2015
DOI: 10.5487/tr.2015.31.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy Induced by Zinc Oxide Nanoparticles in Rats Assessed by Micro-computed Tomography and Histopathology

Abstract: Nanotechnology has advanced at an extremely rapid pace over the past several years in numerous fields of research. However, the uptake of nanoparticles (NPs) into the body after administration through various routes may pose a risk to human health. In this study, we investigated the potential ocular toxicity of 20-nm, negatively- charged zinc oxide (ZnO) NPs in rats using micro-computed tomography (micro-CT) and histopathological assessment. Animals were divided into four groups as control group, ZnO NPs treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Zinc oxide (ZnO) NPs have been extensively applied to cosmetics including sunscreens, pharmaceuticals, semiconductors, dental fillings, and food additives owing to their antibacterial, antifungal, and anti-corrosive properties (57). With the expanded use of ZnO NPs, there might be human health problems because of this inadvertent exposure to them (8,9). Several researchers have reported that ZnO NPs could accumulate and/or damage major internal organs including the central nervous system via several routes (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO) NPs have been extensively applied to cosmetics including sunscreens, pharmaceuticals, semiconductors, dental fillings, and food additives owing to their antibacterial, antifungal, and anti-corrosive properties (57). With the expanded use of ZnO NPs, there might be human health problems because of this inadvertent exposure to them (8,9). Several researchers have reported that ZnO NPs could accumulate and/or damage major internal organs including the central nervous system via several routes (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, our histopathological examination for skin indicated that TiO2 NPs, GST did not penetrate into the skin layer (epidermis including stratum corneum/lucidum/granulosum/spinosum/basale). http://eaht.org Kim et al reported that histopathological finding showed the retinopathy in the eyes from animal treated with ZnO for 90 days and the presence of NPs was identified using micro-CT analysis method [11]. Considering this study, further study like repeated toxicity is thought to be needed to confirm whether presence or treatment-related effect for GST is observed or not.…”
Section: Histologymentioning
confidence: 87%
“…Kim et al reported that histopathological finding showed the retinopathy in the eyes from animal treated with ZnO for 90 days and the presence of NPs was identified using micro-CT analysis method [ 11 ]. Considering this study, further study like repeated toxicity is thought to be needed to confirm whether presence or treatment-related effect for GST is observed or not.…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…The histopathological examination was performed to identify the treatment-related effects for treatment group. Considering retinopathy finding (presence of nanomaterials) observed in previous research of ZnO (particle size: 20 nm, charge: negative) for 90-day in rats [15], we examined the eyes carefully including harderian gland and there were no TiO2-related effects as Figure 5. Also, skin exposed with TiO2, there were no treatment-related changes considered to be toxicological lesion occurred by test substance administration as Figure 6.…”
Section: Histopathological Examinationmentioning
confidence: 99%